Aksesibilitas Pemustaka Penyandang Disabilitas Di Dinas Kearsipan Dan Perpustakaan Provinsi Sumatera Barat Berdasarkan Standar IFLA Checklist - Dimas Muhammad Pambudi; Nurizzati Nurizzati (Journal of Creative Student Research, 2024)
This research aims to analyze the accessibility of library and archives services for people with disabilities in the West Sumatra Provincial Archives and Library Service, the accessibility of users with disabilities in the West Sumatra Province Archives and Library Service based on IFLA Checklist standards, and the obstacles faced in fulfilling accessibility for people with disabilities at the Provincial Archives and Library Service West Sumatra. This research uses qualitative research with descriptive methods. Data collection techniques use observation, interviews and documentation studies. The data validation technique uses triangulation, namely triangulation of data sources. The data validation technique uses the Miles and Hubermen model which consists of data reduction, data presentation, drawing conclusions and verification. The results of this research are as follows. Firstly, accessibility at the West Sumatra Provincial Archives and Library Service has not yet been fully realized because there are still many shortcomings found in the implementation of accessibility services for people with disabilities, such as the ease of library users in meeting their needs has not been fully realized and the only library material collections available are books with braille printing. Second, accessibility at the West Sumatra Archives and Library Service based on the IFLA Checklist Standard reached 40.54%. Thus, it can be said that accessibility for users with disabilities in the Archives and Library Service is still not in accordance with the IFLA Checklist standards. The research results from the IFLA Checklist standard amounted to 111 items which were 45 items which were appropriate while which were 66 items which were not appropriate. Third, the obstacles faced by the West Sumatra Province Archives and Library Service in fulfilling accessibility for disabled users from various aspects such as the lack of available funding, lack of technical knowledge of implementation, and limited human resources who are competent in providing services for users with special needs or disabilities.